Emerging Contaminants in Water: A Review of Detection and Remediation Techniques - Pathak, Vishal; Bhardwaj, Kumar Kinjalk; Prabhakar, Prem (AG Volumes, 2023)
The enduring nature and possible health hazards posed by emerging contaminants (ECs) in water sources have sparked worldwide alarm. The development of enhanced remediation techniques is imperative, as conventional water treatment procedures may not always be sufficient to eliminate these contaminants. This study discusses many ways of detection and treatment, with a focus on nanotechnology, membrane filtration, and photocatalysis. Photocatalytic breakdown using semiconductor materials like titanium dioxide and metal-organic frameworks has been shown to work very well under UV and visible light. Moreover, micropollutants may be efficiently removed by membrane filtration techniques like as reverse osmosis and ultrafiltration. The study emphasises sustainable and ecologically friendly synthesis methodologies as a mechanism for nanomaterials to enhance pollutant degradation. Despite promising advancements, further optimisation is required for practical applications in the areas of increasing catalyst stability, cutting costs, and widespread implementation. Multidisciplinary research may help to solve these problems and provide sustainable water treatment solutions. To reduce the impact of ECs on aquatic ecosystems and human health, it is critical to incorporate hybrid technologies and examine their environmental and economic feasibility.